Mphoto Photography Tutorial Application - Hafit, Hanayanti; Lee Jia Yiing (Applied Information Technology And Computer Science, 2020)
Mphoto Photography Tutorial Application is developed to solve the learning problems in mobile photography. It is aimed to design a platform for young generation who interested in mobile photography to learn photography. Platform used in this project is Android Studio and Firebase. This application contains various functions such as login, register; view or watch tutorial; create, view, update, delete the post; label or score photo; view, edit the personal information and chat with other users. The methodology used in this project is Object-Oriented Software Development (OOSD). This application enables the target users to have a platform to learn, to interact and to involve in photography.